Hepatic angiomyolipoma: A case report and literature review. (2020) - Günster, Simone A.; Kim, Mia; Lock, Johan F.; Krajinovic, Katica
Highlights: HAML is a rare mesenchymal liver tumour which belongs to the family of perivascular epithelioid cell tumours. HAML is typically composed of blood vessels, smooth muscle, and adipose cells. HAML is characteristically positive for HMB-45. In patients with symptoms, uncertain diagnosis, or tumour growth, surgical resection should be performed. Abstract: Introduction: Hepatic angiomyolipoma (HAML) is a rare mesenchymal liver tumour which belongs to the family of perivascular epithelioid cell tumours (PEComas). It is typically composed of blood vessels, smooth muscle, and adipose cells, and shows strong immunoreactivity for HMB-45. Presentation of the case: A 57-year-old woman was referred to our hospital with an unclear liver lesion. A fine needle biopsy revealed a suspicion of hepatic angiomyolipoma with extramedullary haematopoiesis. Preoperative imaging revealed a tumour 17 cm in diameter in the left liver lobe segments II and III. A lobectomy of the left lobe segments II and III was performed. The pathological diagnosis of hepatic angiomyolipoma was obtained. Discussion: Variations in the predominance of the tissue components in HAML impedes diagnosis based on imaging alone. The most promising evidence of HAML is the histological identification of lipomatous, myomatous, and angiomatous tissue combined with immunohistochemical positivity for HMB-45. Although the tumour is considered benign, some cases have been described with malignant behaviour. Surgical resection should be considered in case of symptoms, inconclusive biopsy, or growth in follow-up. Other surgical indications may include aggressive patterns such as vascular invasion, p53 immunoreactivity, or rapidly proliferating tumour cells. Conclusion: HAML is a rare liver tumour. In patients with symptoms, uncertain diagnosis, or tumour growth, surgical resection should be performed according to oncological criteria.